Strategi Digital Marketing Untuk Meningkatkan Daya Saing UMKM - Alinni May Indry Saputri; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Digital marketing is a marketing strategy that uses digital media as wellas internet technology to make it easier to sell and promote goods to consumers. Marketing strategies are also very effective because they can provide a very important role for the progress of UMKM development. This research method uses a qualitative descriptive method. This research shows that digital marketing strategies must be innovative and creative to consider changes in consumer behavior and technological advances in this digital era. This purpose of this research is to see how much influence digital marketing has on business development and competitiveness in UMKM. This can allow UMKM to effectively take advantage of available opportunities, both in the import and export markets, and be able to compete with competitors. So, business succes in the future not only depends on language technology, but also on its ability to innovate to adapt by having accurancy.